Regional Economic Outlook, May 2010, Western Hemisphere : Taking Advantage of Tailwinds. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2010)
A multispeed global recovery is under way, with some emerging markets in the lead and the major advanced economies growing more slowly. This macroeconomic setting has brought a return to easy global financial conditions and high commodity prices-a situation likely to be sustained for some time but unlikely to be permanent. Against that external backdrop, the recovery in the Latin America and Caribbean region overall is advancing faster than anticipated, but moving at different speeds across countries. The report discusses the varying policy challenges that different countries face as the global recovery proceeds. Chapter 1 analyzes the global setting and the outlook for the United States and Canada in particular, while Chapter 2 focuses on the outlook for Latin America and the Caribbean. Chapter 3 looks in depth at the challenges arising from the return of easy external financial conditions. Together with high commodity prices, such conditions represent favorable "tailwinds" for many countries of the region, but also carry risks for policymakers to address.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet